HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MENJALANI HEMODIALISA PADA PASIEN DENGAN GAGAL GINJAL KRONIK DI RUMAH SAKIT SANTA ELISABETH BATAM KOTATAHUN 2022 - Lilis Novitarum; Amnita Ginting; Mardiati Br. Barus; Yetty Lentina Sitorus (Bajang Institute, 2024)
Chronic kidney failure is a disease of decreased kidney function either suddenly or chronically. Treatment of chronic kidney failure can be done in 2 ways with conservative measures and dialysis or kidney transplantation. One of the major problems that contribute to hemodialysis failure is the problem of patient compliance. Family support is one of the factors that affect patient compliance in undergoing hemodialysis therapy. The purpose of this study is to determine the relationship between family support and adherence to dialysis in patients with chronic kidney failure at the Hemodialysis Unit of Rumah Sakit Santa Elisabeth Batam Kota. This research is an analytic observational study with a cross sectional approach. The population in this study were all patients undergoing hemodialysis therapy at the Rumah Sakit Santa Elisabeth Batam Kota Hospital, totaling 30 people. The sample in this study used a total sample of 30 respondents. The data that has been collected was then analyzed using the Fisher's Exact Test statistical test. The results showed that respondents who received family support were mostly good (53.3%) and respondents who were obedient in undergoing dialysis were 23 respondents (76.7%), while respondents who received low family support were mostly disobedient in undergoing dialysis. dialysis as many as 7 respondents (23.3%). Based on the analysis of Fisher's Exact Test, the results obtained p value = 0.0002 (p <0.05) so that H0 is rejected and Ha is accepted which shows that there is a relationship between family support and adherence to dialysis. There is a relationship between family support and adherence to dialysis in the Hemodialysis Unit of the Elisabeth Hospital Batam kota.